2005
DOI: 10.1002/rcm.1824
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of primary monoatomic with primary polyatomic ions for the characterisation of polyesters with static secondary ion mass spectrometry

Abstract: Static secondary ion mass spectrometry (S-SIMS) emerges as one of the most adequate methods for the surface characterisation of polymers with an information depth of essentially one monolayer. The continuing search for increased analytical sensitivity and specificity has led to exploring the use of polyatomic primary ions as an alternative to the traditionally applied monoatomic projectiles. As part of a systematic investigation on polyatomic bombardment of organic and inorganic solids, this paper focuses on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…The strong presence of the Si + mass peak indicates the polymer film was a thin layer, in the order of 1 nm, or there was patchy coverage. Nevertheless, the SSIMS spectrum was in close agreement to those obtained in the previous studies [9,17] -3) and 'C t ' = mass peaks which are unrelated to PHB (see text).…”
Section: Pclsupporting
confidence: 90%
See 3 more Smart Citations
“…The strong presence of the Si + mass peak indicates the polymer film was a thin layer, in the order of 1 nm, or there was patchy coverage. Nevertheless, the SSIMS spectrum was in close agreement to those obtained in the previous studies [9,17] -3) and 'C t ' = mass peaks which are unrelated to PHB (see text).…”
Section: Pclsupporting
confidence: 90%
“…[17]. It is interesting to note that fragments with n > 1 were not seen in PCL for m/z 120-300, as shown in Fig.…”
Section: Pclmentioning
confidence: 84%
See 2 more Smart Citations
“…Some examples include work by Davies et al (2003), who found enhancement in signals characteristic of PET and polypeptides when employing Au þ 3 clusters, Nagy and Walker who observed similar enhancements using Au (Nagy, Gelb, & Walker, 2005) and Bi (Nagy & Walker, 2007) clusters for bombardment of polystyrene and other organic materials, and several others [Au clusters (Bryan et al, 2004;Aimoto et al, 2006;Zhu & Kelley, 2006), C 60 Hill & Blenkinsopp, 2004), SF þ 5 (Gillen & Roberson, 1998;Stapel, Thiemann, & Benninghoven, 2000;Stapel & Benninghoven, 2001;Boschmans, Van Royan, & Van Vaeck, 2005;Van Royen, Taranu, & Van Vaeck, 2005)]. …”
Section: A Static Sims Of Polymersmentioning
confidence: 92%